Copper Oxide Nanoparticles as Delivery Vehicles for Different Pt (II)-Drugs: Experimental and Theoretical Evaluation - Abdelkareem, Shahdan (AUC Knowledge Fountain, 2025)
Platinum(II)-based chemotherapeutic agents such as cisplatin, oxaliplatin, and nedaplatin are mainstays in the treatment of a wide range of solid tumors, yet their clinical application is severely restricted by rapid degradation, poor bioavailability, and dose-limiting side effects. These challenges arise in part from the drugs’ susceptibility to premature hydrolysis, off-target interactions in the bloodstream, and degradation in the gastrointestinal tract, which collectively limit their ability to reach and act on tumor cells. To address these limitations, we explored the use of copper(II) oxide nanoparticles (CuO NPs) as nanocarriers for platinum(II) drugs, aiming to enhance drug stability, loading, and controlled release. We systematically investigated the adsorption, interaction, and release behavior of cisplatin, oxaliplatin, and nedaplatin on CuO NPs using a suite of experimental techniques (UV–Vis spectroscopy, FTIR, BET surface area analysis, XRD, SEM) alongside periodic DFT calculations to elucidate the molecular-level mechanisms of drug-nanoparticle interaction. Our results demonstrate that cisplatin exhibits the strongest affinity for the CuO surface, achieving the highest entrapment efficiency (52%) and adsorption capacity (949 mg/g) among the tested drugs. DFT simulations reveal that cisplatin forms highly stable tri- coordinated bonds with surface copper atoms (adsorption energy: –1.8 eV), in contrast to oxaliplatin and nedaplatin, which display weaker binding and lower loading. The drug release studies further highlight the advantages of this system: cisplatin-CuO nanoparticles display a markedly sustained and controlled release profile, with only ~32% of the drug released over 72 hours, compared to the rapid and nearly complete release observed for free cisplatin under the same conditions. This controlled release is attributed to the strong coordination between cisplatin and the CuO surface, as well as the mesoporous structure of the nanoparticles, which together slow drug diffusion and hydrolysis. This research further studies the viability of green-synthesised CuO NPs as eco-friendly, cost-effective alternatives to commercial variants for platinum drug delivery, combining comparable performance with enhanced sustainability. The best two drugs (Cisplatin and Oxaliplatin) that showed better interactions with the CuO NPs surface were further studied using green synthesized nanoparticles. Green-synthesized CuO NPs also demonstrated substantial, though lower, loading performance, with cisplatin achieving 28.3% entrapment efficiency and 517 mg/g adsorption capacity. These results underscore the superior compatibility of cisplatin with CuO carriers and highlight the potential of both commercial and green-synthesized CuO NPs for platinum drug delivery.